2016
DOI: 10.1097/md.0000000000003128
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Autonomic Dysfunction Predicts Diabetic Foot Ulcers in Patients With Type 2 Diabetes Without Diabetic Polyneuropathy

Abstract: We investigated the factors that might influence the development of diabetic foot ulcers (DFUs) in type 2 diabetes patients without diabetic polyneuropathy (DPN).From January 2000 to December 2005, a total of 595 patients who had type 2 diabetes without DPN between the ages of 25 and 75 years, and had no prior history of DFUs were consecutively enrolled in the study. A cardiovascular autonomic function test was performed to diagnose cardiovascular autonomic neuropathy (CAN) using heart rate variability paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…Various studies have also reported the average age of patients with DFU as between 40-55 years. 19,21,23 There is no significant reason for DFU incidence in middle-age persons but this can be due to the higher prevalence of diabetes in middle-age than in other age groups. In addition, although the quality of diabetes care in women appears to be higher than in men, the prevalence of DFU in women is higher than in men, which may be due to cultural differences in access to healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have also reported the average age of patients with DFU as between 40-55 years. 19,21,23 There is no significant reason for DFU incidence in middle-age persons but this can be due to the higher prevalence of diabetes in middle-age than in other age groups. In addition, although the quality of diabetes care in women appears to be higher than in men, the prevalence of DFU in women is higher than in men, which may be due to cultural differences in access to healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…A study over 5 years of 595 patients with T2DM showed that the development of foot ulcers was independently associated with CAN after adjustment for possible confounding factors (normal vs definite CAN, HR 4.45, 95% CI 1.29–15.33) 94. In addition, a study by Chahal et al suggested that there may be an association between sudomotor dysfunction and peripheral artery disease, which can contribute to foot ulceration and lower-limb amputations 95.…”
Section: Clinical Manifestations and Consequences Of Canmentioning
confidence: 99%
“…29,30 Those with cardiovascular autonomic neuropathy were more likely to also have worse motor and sensory nerve function, 31 diabetic peripheral neuropathy, 28 and were more likely to develop diabetic foot ulcers. 32 Additionally, increasing severity of cardiovascular autonomic neuropathy has been linked to a higher prevalence of peripheral neuropathy. 33,34 However, the relationship between sensorimotor and cardiovascular autonomic function is largely unexplored in general populations of older adults, and examining this relationship was the aim of our study.…”
Section: Introductionmentioning
confidence: 99%